Integrating Broussonetia papyrifera and Two Bacillus Species to Repair Soil Antimony Pollutions - Huang, Huimin; Fan, Li; Zhao, Yunlin; Jin, Qi; Yang, Guiyan; Zhao, Di; Xu, Zhenggang (Frontiers in Microbiology, 2022)
Microbial enhanced phytoremediation technology has become a new way to remediate contaminated soil, which is environmentally friendly, efficient, low-cost, and non-secondary pollution. This study explored the potential of Bacillus cereus HM5 and Bacillus thuringiensis HM7 (B. cereus HM5/ B. thuringiensis HM7) in combination with Broussonetia papyrifera (B. papyrifera) to repair Antimony (Sb) polluted environment through pot experiment. B. cereus HM5/ B. thuringiensis HM7 were inoculated in the rhizosphere of B. papyrifera with the different Sb treatments (0 mmol/L, 100 mmol/L, antimony slag), the growth, root structure, root activity, leaf physiological and biochemical characteristics of B. papyrifera were determined, the changes of soil composition before and after the experiment were also measured. The results showed that the total root length, root volume, tips, forks, crossings and root activities of B. papyrifera with inoculation were higher than those of the control group, and the strains promoted the plant absorption of Sb from the soil environment. Besides, B. cereus HM5/ B. thuringiensis HM7 reduced the content of malondialdehyde, proline and soluble sugars in plant leaves, keeping the antioxidant enzyme activity of B. papyrifera at a low level, and alleviated lipid peroxidation. Principal component analysis (PCA) showed that the added Bacillus were beneficial to the maintenance of plant root functions and the improvement of the soil environment, thereby alleviating the toxicity of heavy metals. Therefore, the application of B. cereus HM5/ B. thuringiensis HM7 in phytoremediation is very meaningful and could improve the phytoremediation efficiency of heavy metals with B. papyrifera.